Application-level fault tolerance in real-time embedded systems - Afonso, Francisco (2008)
Critical real-time embedded systems need to make use of fault tolerance techniques to cope with operation time errors, either in hardware or software. Fault tolerance is usually applied by means of redundancy and diversity. Redundant hardware implies the establishment of a distributed system executing a set of fault tolerance strategies by software, and may also employ some form of diversity, by using different variants or versions for the same processing. This work proposes and evaluates a fault tolerance framework for supporting the development of dependable applications. This framework is build upon basic operating system services and middleware communications and brings flexible and transparent support for application threads. A case study involving radar filtering is described and the framework advantages and drawbacks are discussed.